Quality engineering design and constuction in Malaysia: A fast disappearing and endangered commodity? - Chiang, Jeffrey C. L., Ir. Assoc. Prof. Dr. (The Institution of Engineers, Malaysia, 2011)
Link to publisher’s home page at http://www.myiem.org.my/